2014
DOI: 10.1111/jace.12815
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Low Partial Pressure of Oxygen Processing of Alkali Niobate: NaNbO3

Abstract: This work focused on the processing of low oxygen partial pressure (low‐pO2) calcination and sintering with respect to NaNbO3 (NN) of one key member in ferroelectric (Na,K)NbO3. The high‐density NN ceramics were successfully prepared without any sintering additives using the low‐pO2 process. Comparing conventional air process, the low‐pO2 calcined NN powders showed lower defect concentration and higher densification. The low‐pO2 sintered NN ceramics had dielectric constant and dielectric loss performance at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 65 publications
4
28
0
Order By: Relevance
“…When compared with the air-sintered NKN, the low pO 2 -sintered NKN samples obtained higher electrical resistivity, which further indicated that a higher amount of alkaline elements was retained in the NKN. Similarly, advantages were also noted in the sintering of the end member NaNbO 3 [67]. These results were consistent with the first principle calculation that was conducted by Shigemi and Wada [68,69], showing that the formation energy of alkaline vacancies increased when the atmosphere changed from air to low pO 2 .…”
Section: Volatility Of Alkaline Elementssupporting
confidence: 88%
“…When compared with the air-sintered NKN, the low pO 2 -sintered NKN samples obtained higher electrical resistivity, which further indicated that a higher amount of alkaline elements was retained in the NKN. Similarly, advantages were also noted in the sintering of the end member NaNbO 3 [67]. These results were consistent with the first principle calculation that was conducted by Shigemi and Wada [68,69], showing that the formation energy of alkaline vacancies increased when the atmosphere changed from air to low pO 2 .…”
Section: Volatility Of Alkaline Elementssupporting
confidence: 88%
“…Studies on sintering have received broad research attention worldwide and continue to be of interest today. [11][12][13][14][15][16] Therefore, developing low-temperature sintering techniques has driven global-wide research in scientific communities and industrial corporations during the past several decades. For many materials like general oxides, the sintering temperature is typically~1000°C, and the time necessary to sinter even a simple pellet of dense material can be up to several hours to several days.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As motivated by the need to design ecofriendly piezoelectric ceramics during the past decade, [3][4][5][6][7][8][9] the exploration of lead-free AFE dielectrics over the lead-containing ones, such as PbZrO 3 -based systems, has also evoked considerable interest. 2,[10][11][12][13][14] The NaNbO 3 -based ceramics have been extensively studied due to the intrinsic AFE nature of NaNbO 3 , which is commonly referred to as P phase (with space group Pbma) at ambient conditions. [15][16][17][18] However, the AFE characteristic double P-E hysteresis loops are rarely observed in these systems due to a metastable ferroelectric (FE) Q phase (with space group P2 1 ma), 18 which displays a comparable free-energy profile with the AFE P phase and can be easily induced, and hence prevent back-switching to the AFE state.…”
Section: Solid Solution I Introductionmentioning
confidence: 99%